2020
DOI: 10.1111/ppc.12526
|View full text |Cite
|
Sign up to set email alerts
|

Psychological problem areas of pregnant women diagnosed with abortus imminens as a result of assisted reproductive techniques: A comparative study

Abstract: The study was to evaluate the anxiety, depressive symptoms, hopelessness, and perceived social support of women who became pregnant using assisted reproductive techniques and who were both diagnosed or not diagnosed with threatened miscarriage (TM). Design and Methods: This comparative and descriptive study was carried out with 194 pregnant women with-TM (96) and non-TM (98). The study data were collected using the Pregnant-Women-Information-Form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Social support includes subjective and objective support, and its utilization. Previous studies have shown that a high level of social support plays a protective role in anxiety during pregnancy (Gümüşsoy et al, 2020;Nath et al, 2019). Social support is also one of the factors that influence risk perception and they are negatively correlated (Rui et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Social support includes subjective and objective support, and its utilization. Previous studies have shown that a high level of social support plays a protective role in anxiety during pregnancy (Gümüşsoy et al, 2020;Nath et al, 2019). Social support is also one of the factors that influence risk perception and they are negatively correlated (Rui et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is a positive relationship between social support and maternal mental health (during pregnancy and postpartum) [42,61]. Also some studies have shown that high levels of social support play a protective role in anxiety during pregnancy [62]. In a study by Kraut et al [63] pregnant women stated that they needed emotional support during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Social support includes subjective and objective support, and its utilization. Previous studies have shown that a high level of social support plays a protective role against anxiety during pregnancy [62,63]. Social support can play a direct protective role in individuals' negative emotions, by helping with behavior and providing emotional support.…”
Section: Implications For Clinical Practicementioning
confidence: 99%